Aplikasi Muzara’ah Dalam Perbankan Syariah - Muhammad Ngasifudin (JESI (Jurnal Ekonomi Syariah Indonesia), 2016)
Indonesia is an agricultural country. Indonesia well-known has fertile land. Almost 50% of Indonesian is in agricultural. Rice is the staple food of Indonesia The Demand of Rice is always increasing in line with the population growth It should be able to make the farmers who live in rural areas become more prosperousAs the developping of Islamic banking in Indonesia is certainly a challenge to participate in developing the sector of agricultural with scheme Muzaraah , with scheme sharing the same benefit, between worker and land owners , because the agricultural sector has not get a place in the world of banking, meanwhile agricultural sector has great potential to get finance